DAI SEBAGAI ULAMA PEWARIS PARA NABI - Hatta Abdul Malik (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2015)
Allah guides people through the presence of the messengers who served as a witness, to give glad tidings and warnings, the Caller of Allah, to teach the Qurâ€™an and the wisdom and to be good role models for human beings. However, as the messenger was gone, the task of the apostles passed on to the scholars or preachers whose task is to invite people to the path of Allah. Therefore, the scholars and preachers, as the spearhead of the spread of Islam, need to know the tasks of the Prophet and also follow the example of the Prophet in carrying out the mandate Allah assigned to him.Â Allah memberikan petunjuk kepada manusia melalui kehadiran para rasul yang bertugas untuk menjadi saksi, memberikan kabar gembira dan peringatan, penyeru agama Allah, mengajarkan al-Qurâ€™an dan hikmah serta menjadi suri tauladan yang baik bagi manusia. Namun, ketika rasul sudah tiada, maka tugas rasul tersebut diwariskan kepada para ulama atau dai yang bertugas untuk mengajak manusia kepada jalan Allah. Oleh karena itu, dai sebagai ujung tombak penyebaran Islam perlu mengetahui tugas-tugas para Nabi dan juga mencontoh Nabi dalam mengemban amanat Allah yang dibebankan kepadanya.